Epidemiologia molecular e caracterização da resistência e virulência de amostras de Staphylococcus aureus provenientes de hospitais da Grande Vitória-ES - Bride, Lais de Lima (2015)
Staphylococcus aureus (S. aureus) is the most common pathogen involved in healthcare-associated infections in Brazil and world. Because of the large ability to produce many virulence factors this microorganism is associated with several cases of infections and diseases with severity variable. The aim of this present study is to analyze aspects like virulence, antimicrobial resistance and molecular epidemiology of 100 S. aureus isolates, coming from five hospitals in Grande Vitória - ES. Using the disc diffusion method was observed a resistance rate above 50% to antimicrobials often used in clinical routine like erythromycin, ciprofloxacin and clindamycin. The gene mecA detection identified 41 methicillin-sensitive Staphylococcus aureus (MSSA) and 59 methicillin-resistant (MRSA), including 29 MRSA SCCmec type II, 19 SCCmecIV and 11 non-typeable MRSA strains. The most prevalent virulence genes in our study were ebpS (78 strains) and fnbA (44 strains). The gene encoding the Panton-Valentine leukocidin (PVL) was detected in 22 isolates. The MSSA strains showed, significantly, more virulence genes related with adhesins expression than MRSA strains. The genotypic analysis of the chromossomic DNA fragmentation profile with restriction enzyme in 59 MRSA strains reveal the presence of eight different genotypes, being two prevalent: the genotype A (37 isolates) which includes all SCCmecII strains and the genotype B contains only SCCmecIV strains. The SCCmecIV isolates showed a greater genotypic diversity, being distributed in seven different genotypes which indicates possible polyclonal origin. The virulence profile of the two dominant genotypes was shown to be specific due to gene ebpS predominance in genotype A and genes fnbB and lukS-F predominance in genotype B. This can reflect the certain genes capacity to insert in some specific lineages. The small number of circulating lineages in studied hospitals indicates the need for improvements in surveillance systems as also in adoption of effective control measures which prevents the dissemination of these lineages between hospitals.